Preparation of novel luminescent nanomicelles responsive to neutrophils and their imaging application in mouse burn model - HU Tao; GUO Jiawei; ZHANG Jianxiang (陆军军医大学学报)
Objective‍　‍To prepare neutrophil-responsive luminescent nanomicelles based on self-luminating compound, luminol, and investigate their imaging capability for a mouse burn model at early stage of inflammation. Methods‍　‍Hexachlorotripolyphosphazene (HCCP) was utilized as the skeleton material to synthesize amphiphilic LHP luminescence materials through chemical synthesis of luminol and polyethylene glycol (PEG). The chemical structure of LHP was characterized using infrared spectrum and nuclear magnetic hydrogen spectrum. Nanomicelle LHP NM was formed by self-assembly of LHP in deionized water, and then its particle size and potential were measured. Transmission electron microscopy (TEM) was applied to observe the morphology of nanomicelles. Optical fiber spectrometer, weak luminescence measuring instrument, and small animal living imager were employed to evaluate the spectroscopic properties, chemiluminescence rules, and in vitro luminescence imaging ability of the nanomicelles. After that, female Balb/c mice were subjected to scalding with hot water at temperatures of 70 ℃, 80 ℃, and 90 ℃, respectively to establish a mouse burn model ranging from degree I to degree II burns. The depth of skin scalds in the model mice was determined through HE staining, while the expression levels of TNF-α, IL-1β, IL-6 and myeloperoxidase (MPO) in the scalded skin tissues were assessed with fluorescence quantitative qPCR. The changes in reactive oxygen species (ROS) levels over time and burn depth in the skin tissues were determined with ROS detection kit. Additionally, the neutrophils within the skin tissues of model mice were labeled with FITC-Ly6G antibody to count the neutrophil number. Finally, a small animal imaging system was utilized to examine the imaging capability of nanomicelle LHP NM in a mouse burn model to analyze the correlation between luminous intensity and number of recruited neutrophil in order to evaluate the effectiveness of luminous nanomicelles for monitoring early inflammatory response and diagnosing burn depth in a mouse burn model. Results　Nuclear magnetic resonance (NMR) spectroscopy confirmed the bonding of approximately 5 luminol units and a polyethylene glycol (PEG) chain to 1 HCCP molecule. TEM and particle size determination results demonstrated that the prepared nanomicelles were spherical, hollow structures in a diameter of around 120 nm. In vitro luminescence experiments revealed that the nanomicelles exhibited high brightness and sustained chemiluminescence under varying concentrations of ROS and MPO levels, with luminescence intensity dependent on both ROS level and nanomicelle concentration. The in vitro cellular experiments demonstrated that the nanomicelles exhibited neutrophil-responsive imaging capability. The luminescence intensity was positively correlated with both the number of neutrophils and the dose of LHP NM, with a linear correlation coefficient (r) of 0.98 and 0.99, respectively. In vivo animal study revealed a significant increase (P<0.05) in the count of neutrophils and ROS level in the skin tissue of burned and scalded mice. Notably, at the time point of 24 h, compared to the 80 ℃ and 70 ℃ treatment groups, the number of recruited neutrophils was increased by 86.4%, and the luminescent imaging intensity rose by 71.5%. These findings indicated that the severity of burns was correlated with the extent of neutrophil recruitment in the injured area, and LHP NM could effectively achieve neutrophil-responsive imaging in model mice. The changes in imaging intensity were closely associated with the number of neutrophils and the level of ROS in the injured skin tissue. Conclusion‍　‍The neutrophil-responsive luminescent nanomicelle LHP NM is successful prepared, and the nanomicelles enable responsive imaging of skin damage in mouse burn model. The luminescence intensity accurately reflects the neutrophil infiltration and ROS level, allowing for real-time monitoring of early inflammatory responses in mouse burn model. Additionally, this study provides methods and strategies for diagnosing burn depth.